Optimizing electric vehicle charging station locations: a study on a small outlying island in Hong Kong - Lau, Yui-Yip (2024)
Electric vehicles (EVs) have been widely considered an essential element to contribute to green and smart transportation, which will further enhance the development of smart cities. Hong Kong, as one of the largest metropolises in the world, has promoted the deployment of EVs for both the private and public transportation sectors over the past decade, with substantial financial subsidies and encouraging policy incentives. With the rapid penetration of EVs, especially in the market of private passenger cars, Hong Kong may face the challenge of insufficient charging facilities in the next few years. As such, the research study aims to develop a mathematical model using a topological method to map out feasible locations for new EV charging facilities on Ap Lei Chau Island, to construct a small Python program to optimize the mapping process of these feasible locations, and to estimate energy consumption and associated economic analysis to foster the spatial planning of EV charging facility networks. In conclusion, optimal locations for new charging facilities for EVs have been revealed to match the rapid growth of EV usage and facilitate the emergence of green and smart transportation.